Functional and Clinical Significance of the Integrin Alpha Chain CD49d Expression in Chronic Lymphocytic Leukemia - Dal Bo, Michele; Tissino, Erika; Benedetti, Dania; Caldana, Chiara; Bomben, Riccardo; Del Poeta, Giovanni; Gaidano, Gianluca; Maria Rossi, Francesca; Bulian, Pietro; Zucchetto, Antonella; Gattei, Valter (Current Cancer Drug Targets, 2016)
Chronic lymphocytic leukemia (CLL) is a clinically heterogeneous disease characterized by the accumulation/expansion of a clonal population of neoplastic cells with the morphological appearance of small mature B lymphocytes in blood, bone marrow, and lymphoid organs. CD49d, the α chain of the α4β1 integrin heterodimer, is one of the main interactors between CLL cells and accessory cells in the microenvironmental sites and one of the main predictors of overall survival. In particular, CD49d is known to play a pivotal role in mediating both cell-cell and cell-matrix interactions in CLL-involved tissues eventually delivering prosurvival signals and protecting CLL cells from drug-induced damages. Treatment strategies targeting the α4β1 integrin could represent an interesting option in CLL. In this context, the recombinant anti-CD49d antibody natalizumab demonstrated the potential to overcome stromal cell-induced resistance of B cell lymphoma cells against cytotoxic drugs and rituximab in vitro. Moreover, a specific interest for the CD49d molecule raises from the clinical activity of the recently proposed inhibitors of kinases downstream the BCR that has been recently related with the inside-out activation of the α4β1 integrin. In the review, we addressed in detail the role of CD49d in CLL cells, including clinical impact, relationship with specific cytogenetic features, and CD49d-dependent interactions in lymph node and bone marrow microenvironment responsible for growth- and survival- supporting signals, eventually influencing CLL prognosis and therapeutic options.
Keywords: CD49d